Spatial analysis of environmentally sensitive areas in Kuala Selangor district, Malaysia - Asmawi, M. Zainora; Ibrahim, Illyani; Abdullah, Fadzidah; Paiman, Tuminah (2016)
This paper addresses the issue of conserving the important areas known as environmentally sensitive areas in Kuala Selangor District, Malaysia. Presently, the existence of these natural elements which are also considered as environmental goods to the community faces a prolong development pressure, regardless its role in enhancing the quality of life. Therefore, this research was embarked to conduct the spatial analysis mapping on the importance of environmentally sensitive areas found in Kuala Selangor. The study highly employed the collection of secondary information regarding textual and statistical data in the form of GIS/MapInfo format to assemble the relevant data for mapping purpose via the sieving technique. The results demonstrate that the environmentally sensitive areas could be categorised into natural heritage, disaster risk and life support, ranging from coastal zones, forestry, paddy field, wetland sites and others. It is noticeable that these areas are essential not only concerning its environmental value, but also supports the economic growth of Kuala Selangor. In this regards, the identification of these areas is crucially needed for both the quality and quantity of stock for a longer run. As a conclusion, it is evident the identification of environmentally sensitive areas in Kuala Selangor has benefited many stakeholders involved in the planning and management of the district of Kuala Selangor.